1995
DOI: 10.1093/infdis/172.3.764
|View full text |Cite
|
Sign up to set email alerts
|

Control of Sexually Transmitted Diseases in Haiti: Results and Implications of a Baseline Study among Pregnant Women Living in Cite Soleil Shantytowns

Abstract: Women attending Haitian slum-based antenatal clinics were evaluated for sexually transmitted diseases (STDs): 110 (11%) of 996 were syphilis seroreactive, 313 (35%) of 903 had trichomoniasis, 110 (12%) of 897 had gonococcal or chlamydial cervical infection (or both), and 418 (47%) of 891 had at least one STD. Syphilis seroreactivity was associated with illiteracy (P = .007), lower socioeconomic status (P < .001), and a history of spontaneous abortion (P = .02). Of 663 evaluated sera, 56 (8%) had human immunode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 11 publications
0
22
0
5
Order By: Relevance
“…[16][17][18] The STD prevalence rate found in the rural Artibonite Valley is surprisingly close to the STD prevalence rate found in pregnant women in Cite Soleil, an urban slum of Port au Prince. 19 The prevalence rate of cervical infection was 12% in both areas; the prevalence rate of syphilis was 7% in rural Haiti versus 11% in urban Haiti. In rural Haiti, 40% of women had at least one STD compared with 47% in urban Haiti.…”
Section: Discussionmentioning
confidence: 90%
“…[16][17][18] The STD prevalence rate found in the rural Artibonite Valley is surprisingly close to the STD prevalence rate found in pregnant women in Cite Soleil, an urban slum of Port au Prince. 19 The prevalence rate of cervical infection was 12% in both areas; the prevalence rate of syphilis was 7% in rural Haiti versus 11% in urban Haiti. In rural Haiti, 40% of women had at least one STD compared with 47% in urban Haiti.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, previous studies have shown that the prevalence of STDs among women of lower economic status reaches 40.1-47%. 12,13 The low number of males presenting with STDs might be explained by economic limitations (e.g., difficulty in obtaining a day off work for visiting the clinic), cultural issues, and also, some overdiagnosis of STDs in females.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaires were based on prior literature that documented risk factors for STDs in Haiti. 22,23 In addition to laboratory diagnosis of chlamydia and gonorrhea, HIV status was determined using the ELISA test. A more detailed description of the methods for this study of STDs is provided by Smith Fawzi et al 24 …”
Section: Study Population Design and Data Collectionmentioning
confidence: 99%